Thyroid hormone receptor orthologues from invertebrate species with emphasis on Schistosoma mansoni - Wu, Wenjie (BioMed Central, 2007)
BACKGROUND: Thyroid hormone receptors (TRs) function as molecular switches in response to thyroid hormone to regulate gene transcription. TRs were previously believed to be present only in chordates. RESULTS: We isolated two TR genes from the Schistosoma mansoni and identified TR orthologues from other invertebrates: the platyhelminths, S. japonium and Schmidtea mediterranea, the mollusc, Lottia gigantean and the arthropod Daphnia pulex. Phylogenetic analysis of the DNA binding domain and/or ligand binding domain shows that invertebrate and vertebrate TRs cluster together, TRs from the vertebrates and from the jawless vertebrate (lamprey) clustered within separate subgroups, Platyhelminth TRs cluster outside of the vertebrate TR subgroups and that the schistosome TRs and S. mediterranea TRs clustered within separate subgroups. Alignment of the C-terminus of the A/B domain revealed a conserved TR-specific motif, termed TR 'N-terminus signature sequence', with a consensus sequence of (G/P)YIPSY(M/L)XXXGPE(D/E)X. Heterodimer formation between S. mansoni TRs and SmRXR1 suggests that the invertebrate TR protein gained the ability to form a heterodimer with RXR. ESMA analysis showed that SmTRα could bind to a conserved DNA core motif as a monomer or homodimer. CONCLUSION: Vertebrate TR genes originated from a common ancestor of the Bilateria. TR genes underwent duplication independently in the Protostomia and Deuterostomia. The duplication of TRs in deuterostomes occurred after the split of jawless and jawed vertebrates. In protostomes, TR genes underwent duplication in Platyhelminths, occurring independently in trematode and turbellarian lineages. Using S. mansoni TRs as an example, invertebrate TRs exhibited the ability to form a dimer with RXR prior to the emergence of the vertebrate TRs and were able to bind to vertebrate TR core DNA elements as a monomer or homodimer.